Assessment of sleep quality in the Intensive Care Unit: A comprehensive review of tools and techniques: Assessment of sleep quality in the ICU: A comprehensive review of tools and techniques - Lao-amornphunkul, Suchanun; Raykateeraroj, Nattaya; Kitisin, Nuanprae (Clinical Critical Care, 2025)
Sleep disturbances are common among critically ill patients, significantly impacting recovery and overall health outcomes. Sleep in the Intensive Care Unit (ICU) is often fragmented, with reduced deeper sleep stages and disrupted circadian rhythms. This review explores a range of tools for assessing sleep quality in ICU settings, including both objective and subjective methods. Objective tools, such as polysomnography (PSG), Bispectral Index (BIS), and actigraphy, provide quantifiable data on sleep patterns but vary in their practicality and accuracy. PSG is considered the gold standard due to its comprehensive measurement of sleep stages; however, its use is limited in ICU settings due to high costs, complexity, and the need for trained personnel. BIS and actigraphy offer more feasible alternatives, but their validity and accuracy compared to PSG can vary. Subjective approaches, like patient questionnaires and nurse observation tools, offer valuable insights into perceived sleep quality but may be influenced by patient condition and cognitive status. This review evaluates the advantages, limitations, validity, and reliability of these tools, emphasizing their potential roles in clinical practice. The findings suggest the need for more tailored approaches to sleep assessment in ICU patients, acknowledging that no single tool is without limitations. Further research is needed to develop novel, reliable, and cost-effective sleep assessment methods specifically suited for the ICU, which could improve patient outcomes through better-targeted interventions for sleep disturbances.